Faktor yang berhubungan dengan perilaku konsumsi tablet fe saat menstruasi pada remaja putri : Consumption of Fe Tablets, Menstruation, Adolescents - eka bati widyaningsih (Politeknik Karya Husada, 2022)
The 2018 Riskesdas results on the proportion of young women who received iron supplement tablets was 76.2% received blood supplement tablets with consumption of < 52 items. The 2017 Indonesia Health Profile showed that the coverage of iron supplement administration to young women in Indonesia was 29.51%. The data in the 2017 Indonesian Health Profile for DKI Jakarta Province is only 6.11%. The results of the validation test conducted on 30 class XI students at SMK Kartika X-2 Jakarta found that 18 people had less Fe tablet consumption behavior during menstruation. The purpose of this study was to determine the factors associated with the consumption behavior of Fe tablets during menstruation in class XI female adolescents at SMK Kartika X-2 South Jakarta in 2019. This research is a quantitative descriptive study with a cross-sectional approach. The research was conducted from 16 to 17 July 2019. The population in this study were all 194 class XI students and the samples in this study were some class XI students, totaling 91 respondents. The data in this study are primary data and the analysis was carried out using univariate and bivariate methods. The results of the study from 91 respondents showed that there was a relationship between knowledge (p-value = 0.0005) and attitude (p-value = 0.0005) with the consumption behavior of Fe tablets during menstruation in young women. While parental education (p-value=0.667), family income (p-value=0.104), family support (p-value=1.000), teacher support (p-value=0.443), friend support (p-value=1.000) with the consumption behavior of Fe tablets during menstruation in female adolescents. With this research it is hoped that the government program regarding the consumption of blood-supplemented tablets during menstruation can run optimally and adolescents can be free from the problem of anemia.